Loss of RNA‐binding motif protein 3 expression is associated with right‐sided localization and poor prognosis in colorectal cancer. Issue 2 (22nd July 2015) - Melling, Nathaniel; Simon, Ronald; Mirlacher, Martina; Izbicki, Jakob R; Stahl, Philip; Terracciano, Luigi M; Bokemeyer, Carsten; Sauter, Guido; Marx, Andreas H
Abstract : Aims: RNA‐binding motif protein 3 (RBM3) has recently been suggested as a prognostic biomarker in an array of human cancers. This study aimed to examine its effects in colorectal cancers. Methods and results: RBM3 expression was analysed by immunohistochemistry on a tissue microarray containing 1800 colorectal cancers (CRCs). Nuclear RBM3 immunohistochemical staining was found in 95.9% of all interpretable CRCs. Loss of RBM3 expression was linked to advanced tumour stage ( P < 0.0001), right‐sided tumour localization ( P < 0.0001), and poor prognosis ( P = 0.0003). In a multivariable analysis including RBM3 staining, tumour grade, tumour stage, and nodal status, only tumour stage and nodal status proved to be independent prognostic markers ( P < 0.0001 each), whereas the prognostic impact of RBM3 staining was not significant ( P = 0.2655). Conclusions: Our observations indicate that loss of RBM3 expression is an unfavourable prognostic marker in CRC, and is linked to right‐sided tumour localization.